PENERAPAN MODEL QUANTUM TEACHING UNTUK MENINGKATKAN KOGNITIF SISWA KELAS V SDN LUENG TAHE - Gusti Handayani (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2024)
This study aims to determine the cognitive improvement of 5th grade students after implementing the quantum teaching model. The research design used is the Classroom Action Research (CAR) type. The subjects in this study were 29 of 5th grade students consisting of 12 female students and 17 male students. Data collection was carried out by observation, field notes and tests. The results of the study in cycle I, the average science score was 47.24, the social studies score was 48.45. In cycle II, the science score was 59.48, the social studies score was 65.34. In cycle III, the science score was 83.45 while the social studies score was 83.10. It can be concluded that the application of the quantum teaching model can improve the cognitive of 5th grade students